What is behind binge-watching? The psychological effects on youth - Nouran Amr; Hanan Gunied; Sally Gad (Insights into Language, Culture and Communication)
Technology has transformed the way people watch television, allowing them to schedule their viewing based on time, content, location, and equipment used. The popularity of Internet-based TV services (such as Netflix, Amazon Video, Apple TV, Watch iT, Shahid VIP, and Hulu) and the production of more sophisticated stories have contributed to the popularisation of a specific TV viewing style known as " binge-watching." The aim of this research is to identify the psychological impacts of binge watching on youth. There are two perspectives on binge-watching. The first is concerned with amusement, good feelings, stress relief, cognition, and passing the time. The second point of view, on the other hand, emphasises the negative implications of binge watching, as well as the symptoms of behavioural addiction, despair, loneliness, and escapism. Purposive Sample was chosen from non-probability sampling by the researcher. As the researcher has certain criteria that she wishes to employ in this study, such as persons who avidly watch TV episodes on internet streaming services such as Netflix. The poll will be conducted among people aged 18 to 35, as this age group is more reliant on technology and social media than others. According to the findings, binge-watching is a two-edged sword with both advantages and disadvantages. We can use it to pass the time or for enjoyment, but at some point, we must be able to regulate it so that we do not injure ourselves. We should manage our time and the quantity of episodes we watch in a single sitting. So, if we restrain ourselves, this will not have a bad impact on us. We can use it as a treat on weekends, but it should not become a habit.     Received:21 August 2023 Accepted: 06 February 2024 Published: 31 March 2024